Smart Dustbin with Segregation System and GSM Module - Die, Tiong Huang; Hikma Shabani, (Progress in Engineering Application and Technology, 2023)
The project's goal is to help garbage collectors while also beautifying the environment. It does not require a large amount of manpower to gather the trash. Money will be saved significantly since they will not have to be paid. Society will become more harmonious because of the clean environment, and these garbage collectors will be cleaner while performing their duties. The purpose of this research is to prototype a smart dustbin with a segregation system using Arduino as the microcontroller. Sensors such as an infrared sensor, a moisture sensor, and an inductive proximity sensor are used to complete this smart dustbin. Moisture sensors and inductive proximity sensors are used to segregate different types of waste, while infrared sensors are used to detect users. Ultrasonic and GSM SIM900A modules are the most important components in the notify system. Smart dustbins with a notification system allow the management to reduce costs because they can easily manage the schedule of collecting the waste according to the notification sent by the smart dustbin. Because all of the systems are automated, human power can be reduced as well. With the limitation of using a power adapter as the supply, future researchers can prototype smart dustbins using a solar panel or battery. In conclusion, this smart dustbin has great potential for the development of smart cities and Industry 4.0.